Gene editing pests and primary industries – legal considerations - Everett-Hincks, Julie; Henaghan, Mark (New Zealand Science Review, 2019)
To explore the implications of gene editing technology for New Zealand, the Royal Society Te Apārangi convened a multi-disciplinary panel of some of New Zealand’s leading experts to consider the social, cultural, legal, ethical and economic implications of revolutionary gene-editing technologies for New Zealand. This brief academic paper is the opinion of the authors, Everett-Hincks and Henaghan, and it informs and is informed by the work of the Royal Society Te Apārangi Gene Editing Panel.